Far infrared cavity of a post C-rich AGB star under IRAS survey - Gautam, A K; Aryal, B (BIBECHANA, 2017)
In this paper, we discuss about the physical properties of the dusty environment around the mass losing carbon rich post AGB star located at R.A. (J2000) =06 h 53m 01s and Dec (J2000) =-02o 16’ 00”, in the far infrared  IRAS maps. A cavity like structure (major diameter ∼ 103.3 pc & minor diameter ∼33.1 pc) is found to lie at R.A. (J2000)= 06 h 51 m 54.02 s and DEC (J2000) =  -01o 35’ 43”, located at a distance ∼ 6.11 kpc from the star. We studied the distribution of flux density, dust color temperature, dust mass  in the cavity. The dust color temperature is found to lie in the range 18.7 K to 20.5 K which shows the cavity is isolated and  independently evolved. Such a low offset temperature variation shows that there is symmetric outflow or symmetric distribution of density and temperature. It further suggests that our structure is bigger in size and is far away from the far infrared loops(kk loops). The cavity may be in thermally pulsating phase.  A possible explanation of the results will be discussed.BIBECHANA 90 (2018) 96